Factor structure of the Brazilian version of Pediatric Daytime Sleepiness Scale - Ferrari Junior G.J.* (2018)
© 2018, © 2018 Taylor & Francis Group, LLC.The present study aimed to analyze the construct validity of the Pediatric Daytime Sleepiness Scale (PDSS) for the evaluation of the daytime sleepiness construct in adolescents through confirmatory factorial analysis. The cross-sectional study was carried out with a sample of 773 adolescents aged 14 to 19 years, enrolled in the state schools of Paranaguá, Paraná, Brazil. We investigated the sex, age, school year, study shift, occupational status, socioeconomic level and daytime sleepiness. The PDSS questions were not normal (p <0.001) and the mean total score was 14.87 (5.62). With Schwarz’s BIC adjustment indicators = 142,389 and Akaike’s AIC = 105,389, the model reached the criteria of the global adjustment indicators of the model in the confirmatory analysis, in which RMSEA = 0.020; CFI = 0.986; TLI = 0.977; SRMR = 0.021, with 17 degrees of freedom, KMO = 0.8504 and Cronbach’s Alpha = 0.737, with three correlations. We conclude that the construct validity of the PDSS remains valid and confirms its factor structure with only one factor. Thereby, it was verified that the operationalization of the construct sleepiness of adolescents through this scale is adequately conceptualized to the behavior of the age group.